IMPLEMENTASI ENTERPRISE RESOURCES PLANNING (ERP) PADA LEMBAGA KEUANGAN MIKRO SYARIAH - Miswan Ansori; Ahmad Fauzan Mubarok (Wahana Islamika: Jurnal Studi Keislaman, 2021)
Technological developments in the financial industry or financial technology require Islamic microfinance institutions to be able to adapt and use technological developments in order to remain competitive with other financial institutions. This study analyzes how the implementation of Enterprise Resources Planning was carried out at the Islamic microfinance institution KSPSS BMT BUS in integrating and automating all business processes that occur at the Islamic microfinance institution. This research method is carried out with descriptive qualitative methods by conducting Value Chain analysis and SWOT analysis. From the research results, it can be concluded that the research results show that the implementation process carried out has several shortcomings, namely high costs, the implementation process that takes a long time, a limited nominal transaction, an open security system, and dependence on the network. However, on the other side of this process, there are also advantages, namely an integrated system of all branches, faster transaction processing, increased company revenue, and a wider partner network.